Halophytes-associated endophytic and rhizospheric bacteria: diversity, antagonism and metabolite production. Issue 2 (1st February 2018) - Bibi, Fehmida; Strobel, Gary Allan; Naseer, Muhammad Imran; Yasir, Muhammad; Khalaf Al-Ghamdi, Ahmed Abdullah; Azhar, Esam Ibrahim
ABSTRACT: In Saudi Arabia, halophytes occupy tidal and intertidal forest ecosystems. They and their associated microflora have immense potential to yield novel and important useful natural products. Three halophytes ( Avicennia marina, Halocnemum strobilaceum, Zygophyllum qatarense ) were targeted for the isolation and identification of populations of endophytic and rhizospheric bacteria having antimicrobial potential. A total 554 bacterial isolates were initially screened against oomycetes fungal pathogens, Phytophthora capsici and Pythium ultimum . Of these, only 57 rhizospheric and endophytic bacteria exhibited inhibition against the targeted bioassay oomycetes . Tentative identification of the bacteria was on the basis of 16S rRNA gene sequences which revealed 92–100% sequence identity to type strains of related species and placed these organisms in six major classes: Actinobacteria, γ-Proteobacteria, Firmicutes, α-Proteobacteria, Flavobacteriia and β-Proteobacteria . When checked for lytic enzyme production, mostly the isolates of Actinobacteria and Firmicutes were potential enzyme producers. Detection of secondary metabolite biosynthetic genes – type I polyketide synthases, type II polyketide synthases and nonribosomal peptide synthetases – confirmed that 21 (35.5%) isolates were positive for at least one type of the biosynthetic gene. In order to identify metabolites, three isolates, Alteromonas australica (EA73), Aidingimonas halophila (EA105) and Halomonas zincidurans (EA127), were selected and subjected to chemical analyses using liquid chromatography–mass spectrometry and gas chromatography–mass spectrometry. Both analyses showed the presence of different bioactive compounds in the culture extracts of isolates some of which are already reported for their diverse biological activities such as 2, 4-Diacetylphloroglucinol. Our results demonstrated that halophytes represent an important source of potentially active bacteria producing antifungal metabolites of medical significance.